2004
DOI: 10.1111/j.1469-8137.2004.01186.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine root distribution and persistence under field conditions of three co‐occurring Great Basin species of different life form

Abstract: Summary• Fine roots of an annual grass, a perennial grass and a perennial shrub were examined. Based on life histories and tissue composition, we expected the greatest root persistence for the shrub and shortest for the annual grass.• Roots were observed with minirhizotrons over 2 yr for number, length and diameter changes. A Cox proportional hazard regression correlated root persistence with soil water, depth, diameter and date of production.• In 2001, grass roots had similar persistence times, but shrub root… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
44
2
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(52 citation statements)
references
References 49 publications
(83 reference statements)
4
44
2
2
Order By: Relevance
“…Alternatively, our findings could provide evidence of higher lifespan of fine roots of L. divaricata relative to those of S. tenuis, probably induced by high concentration of soluble phenolics (Rodríguez et al 2007). Many studies reported increased fine-root lifespan associated with increased concentration of soluble phenolics (Ryser and Lambers 1995;Van der Krift and Berendse 2002;Peek et al 2005). Additionally, lower fine-root biomass in mixed patches than the sum of the fine-root biomass in both L. divaricata and S. tenuis patches could indicate a limited fine-root carrying capacity of the upper soil.…”
Section: Discussionmentioning
confidence: 95%
“…Alternatively, our findings could provide evidence of higher lifespan of fine roots of L. divaricata relative to those of S. tenuis, probably induced by high concentration of soluble phenolics (Rodríguez et al 2007). Many studies reported increased fine-root lifespan associated with increased concentration of soluble phenolics (Ryser and Lambers 1995;Van der Krift and Berendse 2002;Peek et al 2005). Additionally, lower fine-root biomass in mixed patches than the sum of the fine-root biomass in both L. divaricata and S. tenuis patches could indicate a limited fine-root carrying capacity of the upper soil.…”
Section: Discussionmentioning
confidence: 95%
“…Plants rarely take up water from a single fixed depth throughout the growing season, and often shift their depth of water uptake in response to changing environmental conditions and soil moisture availability. Varying degrees of ecological plasticity (i.e., the capacity to adjust morphological and/or physiological characteristics in response to changing environmental conditions ;Pigliucci 2001;Callaway et al 2003) in rooting functions have been widely documented for plants growing in different ecosystems (Crick and Grime 1987;North and Nobel 1998;Liu et al 2000;Callaway 1990;Ponton et al 2002;Peek et al 2005). However, relatively little attention has focused on assessing ecological plasticity of water uptake dynamics in crop species (Engels et al 1994;Carmi et al 1993;Dardanelli et al 1997;Araki and Iijima 2005).…”
Section: Introductionmentioning
confidence: 97%
“…Despite the endogenous cues, exogenous factors are important for controlling the fine root dynamics and the effects of exogenous factors on fine root dynamics have been received increasingly attention because of the expected climate changes (Kitajima et al 2010). Previous studies have correlated fine root production with water regimes in water-limited shrublands (Peek et al 2005;Palacio and Montserrat-Martí 2007;Padilla et al 2015), and the effects of the soil moisture on the fine root dynamics have been reported to be species specific (Wilcox et al 2004). Shading is another exogenous factor regulating fine root dynamics because root growth and turnover are correlated with photosynthetically active radiation (Fitter et al 1998;Fitter et al 1999;Volder et al 2007).…”
Section: Introductionmentioning
confidence: 99%